Biomimetic materials: A review - Shetty, Suneeth; Manjunath, M.K (International Journal of Medical Research and Review, 2015)
Biomimetics is the science of imitating nature is a growing multidisciplinary field, which is now leading to the fabrication of novel materials with remarkable mechanical properties. It is the study of biological structures, their functions and synthetic pathways emerging at the intersection between cellular biology, molecular biology, material sciences, dentistry and medicine. Bio meaning life and Memesis meaning imitation are derived from Greek words. Perceptions regarding the scope of biomimetics appear to vary widely depending upon the specialized discipline of the investigation. Biomimetics provides a new strategy that translates our knowledge of biological structures and functions and creates new synthetic pathways to mimic biological processes.